Structure Elucidation of the Leaf of Tithonia diversifolia (Hemsl) Gray - Amanatie, Amanatie; Sulistyowati, Eddy (JURNAL SAINS DAN MATEMATIKA, 2015)
Stucture elusidation of the leaves of Tithonia diversifolia (Hemsl) A.Gray, were reported. The compounds were obtained by maceration and analyzed by GC–MS. The compounds of the leaves were the non volatile fractions of the plant are a rich source of Camphene 0, 6 (SI 9.53)., β-pinene 10, 9 (SI 8, 9)., Myrcene 0.8(SI 9, 92)., 1, 8-Cineole0, 91 (SI 1, 03)., β–Caryophyllene 2, 08 (SI 1, 419)., β-Gurjunene0.4(SI1, 428)., α Humulene1.6 (SI 1, 454) Germacrene D 12, 6 % (SI 1, 481), characterized presented the Tithonia diversifolialeaf